ARBOREAS VOCES SOLIS LUNEQUE LOQUENTES: ALEXANDER THE GREAT’S VISIT TO THE TREES OF THE SUN AND THE MOON IN XIITH CENTURY CHRONICLES. - De Toro Vidal, José Miguel (Revista de Historia Social y de las Mentalidades, 2016)
Alexander the Great’s encounter with the talking trees of the Sun and the Moon in a sacred forest of India is one of the many fantastic episodes of his legend. The aim of this paper is to study the moment when the chroniclers decide to include this passage in their works, and to inquire into the reasons for this decision. To do so, we have examined the universal chronicles of the 12th and early 13th centuries, together with others works produced at the time. We can observe that the Historia Scholastica of Peter Comestor and the World maps contributed to the acceptance of the episode. However, the inclusion of this passage is not an assertion of Alexander’s encounter with the trees as a true historical fact, but responds to the historical and literary project planned by the author of each chronicle.